Mapping the bipolar mind through comics: An interview with Ellen Forney. Issue 1 (1st November 2021) - Saji, Sweetha; Venkatesan, Sathyaraj
This is an interview with comics artist Ellen Forney, author of Marbles: Mania, Depression, Michelangelo, and Me: A Graphic Memoir and Rock Steady: Brilliant Advice From My Bipolar Life. In the interview, Forney reflects on her personal experience with bipolar disorder and its representation in the comics medium. The interview also presents recent trends in graphic medicine (intersection of comics and health) and the role and use of visual metaphors in delineating mental illness experiences, through examples drawn from Forney's own work.